2016
DOI: 10.1177/0010414015626445
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness Beyond Policy Satisfaction: Does It Matter to Citizens?

Abstract: Can politicians facilitate citizen acceptance of unwelcome policy decisions by acting responsively during the decision-making process ? We suggest a framework to analyze the responsiveness-acceptance connection and report findings from two studies designed for that purpose. First, we ran a survey experiment to examine how exogenously induced responsiveness actions affect reactions to a policy decision. Second, we conducted a case study to see how results hold up in a real-world setting. We find that responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(135 citation statements)
references
References 52 publications
8
127
0
Order By: Relevance
“…Previous experimental studies on similar topics focus on how various modes of decision making in small-scale settings affect individual assessments of procedural fairness (Tyler 1994;Esaiasson et al 2016b), or decision acceptability (Esaiasson et al 2016a;Arnesen 2017). Previous experimental studies on similar topics focus on how various modes of decision making in small-scale settings affect individual assessments of procedural fairness (Tyler 1994;Esaiasson et al 2016b), or decision acceptability (Esaiasson et al 2016a;Arnesen 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Previous experimental studies on similar topics focus on how various modes of decision making in small-scale settings affect individual assessments of procedural fairness (Tyler 1994;Esaiasson et al 2016b), or decision acceptability (Esaiasson et al 2016a;Arnesen 2017). Previous experimental studies on similar topics focus on how various modes of decision making in small-scale settings affect individual assessments of procedural fairness (Tyler 1994;Esaiasson et al 2016b), or decision acceptability (Esaiasson et al 2016a;Arnesen 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Neblo et al (2010) experimented with Americans' willingness to deliberate and found that many are positively inclined to take part in such activities. More recently, a series of experimental studies investigated the effects of procedures on political legitimacy (Esaiasson et al, 2012(Esaiasson et al, , 2016Persson et al, 2013). Persson et al (2013) studied the effects of direct voting and deliberation on legitimacy beliefs in a field experimental study of small-group decision-making.…”
Section: Decision-making Influence and Outcome Favourability As Legitmentioning
confidence: 99%
“…They also measure to what degree the favourability of the outcome matters to the evaluation of the decisions. As such, the study contributes to an emerging political science literature on experiments with decision-making processes and their impact on legitimacy beliefs (Esaiasson et al, 2012(Esaiasson et al, , 2016Persson et al, 2013). These micro-level empirical studies take a novel and complementary approach in examining a central question in studies of democracy that tend to…”
Section: Introductionmentioning
confidence: 98%
“…More recently, scholars of responsiveness have followed the example of scholars on issue congruence and assess the consequences of policy responsiveness for democratic satisfaction or the acceptability of political decisions (e.g., Arnesen & Peters, ; Esaiasson & Wlezien, ; Esaiasson et al, ). Others examine under which circumstances citizens value and perceive responsiveness (Bowler, ; Rosset, Giger, & Bernauer, ), or responsiveness to particular subgroups in society (Grimes & Esaiasson, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among others, scholars engage in conditional explanations (e.g., Hobolt & Klemmensen, 2008;Wlezien & Soroka, 2012), issues of causality (Hakhverdian, 2012), and differences between population subgroups (e.g., Grimes & Esaiasson, 2014). A smaller and more recent share of the literature uses responsiveness as an independent variable to predict democratic support (e.g., Esaiasson, Gilljam, & Persson, 2017) or tries to explain varying levels of responsiveness with institutional designs or the composition of parliaments (e.g., Bird, Saalfeld, & W€ ust, 2011).…”
Section: Introductionmentioning
confidence: 99%